The Africa Centres for Disease Control public health emergency management fellowship: insights from the inaugural cohort - Getaneh, Mesfin Wossen; Pascal, Albert; Luka-Lawal, Rejoice Kudirat; Kutubana, Martin Kukenzikila; Bunting-Graden, Joseph Anderson; Ezembro, Esmeraldo Tiago Camboneia; Tadicha, Soransora D.; Essone, Paulin N.; Magodi, Simon; Anebonam, Uchenna; Mankoula, Wessam; Oboma, Womi Eteng (Frontiers in Public Health, 2025)
Public health emergencies remain a significant challenge across the African continent, driven largely by the high burden of infectious diseases and constraints in the public health workforce. The Africa Centre for Disease Control and Prevention (Africa CDC) has taken a strategic move towards addressing emergency preparedness and response workforce gap with the implementation of the Public Health Emergency Essone Management (PHEM) Fellowship aimed at providing African Union Member States (MS) with trained personnel in emergency management. We describe the components of this program comprised of six sections such as the advisory committee (from several countries and divers organizations), a rigorous selection process, eleven weeks of in-person classes with validated materials, field deployments in countries with ongoing emergency crises, projects and mentorship programs. The PHEM fellowship offers African countries a strategic opportunity to strengthen their public health workforce and enhance their preparedness towards potential public health emergencies.